Learning, teaching, and researching on the Internet : a practical guide for - Stein, S. D. (Stuart D.) (Harlow, Essex, England ; New York : Addison Wesley Longman, 1998)
Internet preliminaries. Searching the internet. Exchanging views on the internet. Social science subject resources. Closure.
Keywords: Computer network resources; Social sciences; Internet (Computer network); Social sciences -- Computer network resources